HUBUNGAN AKTIVITAS FISIK DAN TINGKAT STRES TERHADAP KUALITAS TIDUR PADA LANSIA DI UPT PANTI SOSIAL TRESNA WERDHA HUSNUL KHOTIMAHPEKANBARU - Muhammad Wildan Adiatama; Sabtria Winda Sari; Riamah Riamah; Swastika Sekar Utami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Elderly are individuals at the end stage of human life, where the process of decline occurs more dominantly than progress (Soetjiningsih, 2019). The purpose of this study is to understand the relationship between physical activity and stress levels on sleep quality in the elderly at UPT Panti Sosial Tresna Werdha Husnul Khotimah Pekanbaru. The study was conducted in the working area of UPT Panti Sosial Tresna Werdha Husnul Khotimah Pekanbaru with a sample size of 73 people. Data collection was carried out using interviews and questionnaires with the total sampling technique for sampling. This research design uses a cross-sectional approach and employs the Chi-Square test. The research was conducted in December 2025. Based on the correlation test between physical activity and sleep quality using the Chi-Square test, the correlation coefficient was (p = 0.001 0.005). From these results, it can be concluded that there is a relationship between physical activity and sleep quality in the elderly at UPT Panti Sosial Tresna Werdha Husnul Khotimah Pekanbaru. Based on the correlation test between stress levels and sleep quality using the Chi-Square test, the correlation coefficient was (p = 0.001 0.005). From these results, it can be concluded that there is a relationship between stress levels and sleep quality in the elderly at UPT Panti Sosial Tresna Werdha Husnul Khotimah Pekanbaru. It is hoped that UPT Panti Sosial Tresna Werdha Husnul Khotimah Pekanbaru can implement ways to improve sleep quality effectively.Keywords: Physical Activity, Stress Levels, and Sleep Quality